Comparative CFD Analysis of NACA 0012 and NACA 4415 Airfoils at Varying Angles of Attack on Aircraft Wings Using ANSYS Fluent - Medyawanti Pane (Universitas Sultan Ageng Tirtayasa, 2025)
During takeoff and approach to land, all aircraft move at low speed and high lift so that the wing is one of the main components of an airplane that has the basic function of being able to produce good aerodynamic performance characteristics so that objects can be lifted and maintain their position in the sky. In this study, an airfoil geometry with the NACA 0012 and NACA 4415 series was tested using ANSYS Fluent software at a speed of 200 m/s. To obtain maximum performance in this geometry, a variation of the angle of attack from 0° to 20°, was given so that the lift and drag force were obtained from each angle of attack. From the simulation and calculation results, the highest lift coefficient and drag coefficient in the NACA 0012 Airfoil simulation are at an angle of attack of 20°, is 0.5106 and 0.07829. Meanwhile, in the NACA 4415 Airfoil simulation, the highest lift coefficient is at an angle of attack of 20°, is 0.64623 and 0.08238.